Aspectos epidemiológicos das parasitoses gastrintestinais de pequenos ruminantes na agricultura familiar no território da Borborema Paraíba - Oliveira, Carlos Felipe Teodoro de (2019)
The objective of this study was to identify the main epidemiological aspects of gastrointestinal parasitoses in the productive systems of family farmers in the territory of Borborema so that efficient forms of control could be delineated. Nine properties located in the municipalities of Algodão de Jandaíra, Solânea and Montadas were visited. Through a semi-structured questionnaire and parasitological examinations of fecesinformation about the about propertiesand contamination of the animals were obtained. The reduction of areas available for grazing in the rainy season, the single and inadequate use of antiparasitic drugs as a form of control, the lack of an integrated control of parasites, the non-use of selective treatments and the proven resistance toantiparasitic drugs are among the main factors associated outbreaks. In 100% of the properties animals with clinical signs of gastrointestinal parasitosis were identified and in 66,67% of these properties of Solânea and Montadas there were deaths, and in 100% of these properties of Algodão de Jandaíra. Outbreaks of parasitosis occur between may and July (rainy season). In the coproculture the predominance of helminths of the genera Haemonchus, Trichostrongylus, Oesophagostomun and Cooperiawere verified. The occurrence of anthelmintic resistance were identified in 100% of the properties. The identified faults in the properties regarding the control of parasites and sanitary management demonstrate the need for a strong extension action, which should include lectures and field activities with rural producers on aspects of sanitary management and awareness of veterinarians working in the aread and in veterinary pharmacies with regard to the practices of integrated control of parasites and the adequate use of anthelmintics.